2014
DOI: 10.1103/physrevd.90.125019
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic superfluidity and vorticity from the nonlinear Klein-Gordon equation

Abstract: We investigate superfluidity, and the mechanism for creation of quantized vortices, in the relativistic regime. The general framework is a nonlinear Klein-Gordon equation in curved spacetime for a complex scalar field, whose phase dynamics gives rise to superfluidity. The mechanisms discussed are local inertial forces (Coriolis and centrifugal), and current-current interaction with an external source. The primary application is to cosmology, but we also discuss the reduction to the nonrelativistic nonlinear Sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(85 citation statements)
references
References 31 publications
1
84
0
Order By: Relevance
“…(20). Based on the numerical computations in refs., 29,30 we find that the first order Coriolis term is the most important. We show that it leads to vortex formation, and therefore that quantum vortices can be generated by the frame-dragging effect of black holes.…”
Section: 6mentioning
confidence: 80%
See 4 more Smart Citations
“…(20). Based on the numerical computations in refs., 29,30 we find that the first order Coriolis term is the most important. We show that it leads to vortex formation, and therefore that quantum vortices can be generated by the frame-dragging effect of black holes.…”
Section: 6mentioning
confidence: 80%
“…Huang had been looking for this solution for a long time as he suggested that the so-called "non-thermal filaments" observed near the center of the Milky Way (where there are super massive black holes) could be parts of vortex rings surrounding the blackholes, as pointed out in ref. 1,9,29,30 In fact the current-current interaction (7) mimics rotation terms with local (space-dependent) angular velocities as shown above in the Kerr metric case, so it is possible to have a vortex-ring lattice as a solution to the NLKG in the Kerr metric. For the gravitational collapse problem of rotating blackholes, the spacetime outside is described by the Kerr metric while the spacetime inside should be the generalization of the Robertson-Walker metric with angular momentum.…”
Section: Vortex-ring Lattice and The Kerson Layermentioning
confidence: 99%
See 3 more Smart Citations